(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stress can be defined as any type of change that causes physical, emotional or psychological strain. Stress is our body’s response to anything that requires attention or action. Everyone experiences stress to some degree.Stress is a feeling of emotional or physical tension. It can come from any event or thought that makes us feel frustrated, angry, or nervous.In short bursts, stress can be positive such as when it helps us avoid danger or meet a deadline. But when stress lasts for a long time, it may harm our health.I try to find out the impact of stress management among students in online classes. Also I have observed the various steps taken by them to avoid the stress to students amid. I collected the data’s through primary and secondary data and I give suggestions to the betterment of studies